Identificação de barreiras na implementação de metodologias ágeis na indústria automóvel - Soares, Daniel Esteves (2020)
The automotive sector is one of the major contributors for the worldwide economy, not being just a vital element in the economy of the industrialized countries, where motor vehicle production and sales are one of the major impellers of the economy in those countries, but also contributes to the growth of other related activities as metallurgy, plastic/rubber, electronics, textiles, etc. thus empowering the global industrialization. The increasing competitive pressure in the sector led to the “projectivization” of product development processes, through defined concepts and organizational frameworks. However, as projects have grown into more dynamic and complex, consequently the ways of managing them should be reconsidered. Agile Project Management emerged within the software industry, but its applicability is theoretically feasible to any industry. This approach despite permitting to meet the rapidly changing requirements through iterative development, and increasing the process efficiency, the companies also face barriers and challenges in its implementation. Although there is literary evidence of barriers observed in the implementation of Agile Methodologies in software development, there is a lack of bibliographic evidence of barriers observed in the manufacturing sector, and almost null in the Automotive Industry. This survey intended to address a literature gap, identifying barriers in the implementation of Agile Methodologies in the Automotive Industry through a questionnaire survey, categorizing them, and detecting their major source, as well as find possible enablers and recommendations to overcome the identified barriers. “Organizational”, and “Knowledge and technology” barriers were found, through the factor “Improper competency management”. It was corroborated the existence of “Institutional” barriers, through the factor “Change predisposition”, and its correlation with the “No obligation” barrier. It was also found a correlation between the factor “Absence of immediate quantifiable benefits” with the “Lack of financial support” barrier, fitting these variables into the “Financial” barrier category. “Organizational support” and “Investment in training” were identified as the main enablers for the Agile Methodologies implementation. Lastly, a flowchart was developed to sequence the possible enablers and recommendations to overcome the identified barriers.